Detection of plasmid-borne β-lactamase genes in extended- spectrum β-lactamase (esbl) and non-esbl-producing escherichia coli clinical isolateso - Cruz,Merlyn C.; Heydra, Cynthia T. (2017)
Increasing frequency of infections caused by antibiotic resistant Escherichia coli strains producing extended-spectrum β-lactamase (ESBL) needs to be addressed by continuous surveillance and accurate detection of specific ESBLs genes for more effective treatment. A total of 71 β-lactam drug resistant isolates (26 phenotypically ESBL-producing and 45 non-ESBL-producing) were observed to carry approximately 23 kb plasmids. These isolates were subjected to β-lactamase gene-targeted PCR to detect plasmid-encoded blaTEM, blaSHV, blaCTX-M group1 and blaCTX-M group9 genes. BLAST analysis of amplicons revealed that plasmid-encoded blaTEM is most prevalent in both ESBL and non-ESBL-producing E. coli isolates. Plasmid-encoded blaSHV gene was only detected in 8 non-ESBL-producing isolates and explanation of such observation awaits additional studies to detect the possibility that the gene could be in the chromosomal DNA or to test the prevalence of the plasmid-encoded gene with more isolates. Twelve isolates of the ESBL-type blaCTX-M were identified from phenotypically identified ESBLs, comparable with 13 isolates detected with blaTEM. This observation suggests that the relatively newly emerging ESBL-type CTX-M is continuously increasing as one of the new β-lactamase derivatives among ESBL-producing E. coli in the clinical setting. This study reveals that there is discrepancy between the results of the phenotypic observation and genotypic analysis showing that the presence of ESBL-associated β-lactamase genes may be undetected when using the conventional phenotypic approach. Mutation in these unexpressed genes may result to ESBL antibiotic resistance, suggesting that the unexpressed and undetected genes may serve as reservoir for ESBL genes.